Videoaulas e software livre : a relação entre softwares, laboratórios e a Rede Nacional de Ensino e Pesquisa - Claro, Victor Oscar Martins (2016)
Our object of study is a videoclasses service (videoaula@rnp) over the Internet, maintained by the National Network of Education and Research (RNP). To approach it will use the Actor- Network Theory. We propose here to look at the crossings between software, public officials and laboratories. The software available for publishing videoclasses by RNP is a Free Software called RIOComposer. This has become a link between free software and distance education. Obviously, this link is not given in a simple way and involves, on our part, a study of the Free Software and the RNP. Besides that, the movement of some laboratories involved with the creation of RIOComposer and other solutions for distance education will be observed. We will monitor the principles that guided the first Free Software developers, as their initial consequences. For that, some authors of social sciences, who proposed to examine the Free Software, will be used. About RNP, we will deal with its various initiatives involving the spread of high-speed networks for the Brazilian academic community and the development of solutions in Information and Communication Technologies. The selected laboratories will be seen in its relations with the Free Software and RNP.